Improving Social Skill of Student with Disability with Interaktif Method : A Literature Review - Kusumawati, Dian; Junaidi, Ahsan Romadlon; Noviati, Ranti; Ediyanto, Ediyanto (Angstrom Centre of Education, 2024)
This descriptive qualitative research was conducted at one of the State Special Schools in Blitar City, observing five students with disabilities. The observation results showed that the students had poor social skills, with mostly nonverbal interactions and limited engagement in school activities. Through a literature review, this study identified interactive learning methods, such as group games, that could potentially improve students' social skills. While these methods have not yet been implemented, recommendations for the integration of these strategies into the curriculum are aimed at enriching learning experiences and reducing social anxiety. This approach is expected to strengthen the social interaction and self-confidence of students with with disabilities.